2005
DOI: 10.1210/jc.2004-2063
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Circulating Androgens in Mid-Life Women: The Study of Women’s Health Across the Nation

Abstract: Circulating SHBG and androgens are most strongly associated with physical characteristics and the metabolic syndrome in women in this community-based cohort. Androgens are related weakly to physical functioning and other symptoms to which they commonly are attributed, such as sexual desire, sexual arousal, and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
6
9

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 50 publications
7
115
6
9
Order By: Relevance
“…It has been reported that circulating total testosterone level was associated with physical function in women aged 49-65 years (15), though a significant association in women aged 42-52 years was not found in another study (16). On the other hand, DHEA-S showed a modest association with physical functioning (16) and an inverse association with degree of physical disability in women (15).…”
Section: ) Physical Functioningmentioning
confidence: 80%
See 3 more Smart Citations
“…It has been reported that circulating total testosterone level was associated with physical function in women aged 49-65 years (15), though a significant association in women aged 42-52 years was not found in another study (16). On the other hand, DHEA-S showed a modest association with physical functioning (16) and an inverse association with degree of physical disability in women (15).…”
Section: ) Physical Functioningmentioning
confidence: 80%
“…Low SHBG level was associated with the occurrence of cardiovascular disease (43, 44). SHBG level was negatively associated with hyperinsulinemia (86) and risk of metabolic syndrome (16,87). We also showed that SHBG level Group A : early reproductive stage, Group B : late reproductive stage, Group C : early menopausal transition, Group D : late menopausal transition, Group E : women for whom less than 1 year has passed since menopause, Group F : women for whom less than 5 years have passed since menopause, Group G : women for whom more than 5 years have passed since menopause was negatively correlated with Homeostasis Model Assessment (HOMA) index in both men and women (88).…”
Section: Action Of Shbgmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies have observed an association between measures of female sexual desire and serum concentrations of total testosterone and free testosterone (3,4), while others could not confirm this (5). Although a biopsychosocial approach to female sexuality remains in order, there seems to be a consensus upon the role of testosterone in motivational aspects of sexuality such as sexual desire (6,7).…”
Section: Introductionmentioning
confidence: 99%